2017
DOI: 10.7717/peerj.3754
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of the spreading and invasion of radial growth phase and metastatic melanoma cells in a three-dimensional human skin equivalent model

Abstract: BackgroundStandard two-dimensional (2D) cell migration assays do not provide information about vertical invasion processes, which are critical for melanoma progression. We provide information about three-dimensional (3D) melanoma cell migration, proliferation and invasion in a 3D melanoma skin equivalent (MSE) model. In particular, we pay careful attention to compare the structure of the tissues in the MSE with similarly-prepared 3D human skin equivalent (HSE) models. The HSE model is identically prepared to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 81 publications
2
61
0
Order By: Relevance
“…After the formation of each compartments, the reconstructed skin is left at the air‐liquid interface allowing keratinocyte differentiation and stratification . Histologically, HSE architecture and composition closely resemble human skin . HSE has been used as an alternative to animal testing for studies of skin barrier function, skin irritation, wound healing, ultraviolet light‐induced damage, for the treatment of burns and other wounds .…”
Section: Melanoma 3d Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the formation of each compartments, the reconstructed skin is left at the air‐liquid interface allowing keratinocyte differentiation and stratification . Histologically, HSE architecture and composition closely resemble human skin . HSE has been used as an alternative to animal testing for studies of skin barrier function, skin irritation, wound healing, ultraviolet light‐induced damage, for the treatment of burns and other wounds .…”
Section: Melanoma 3d Modelsmentioning
confidence: 99%
“…DED is placed on a sterile stainless steel rings with a diameter of 6 mm in a 24‐well tissue plate. Primary keratinocytes, fibroblasts and melanoma cells are seeded together on DED and grown submerged for 24 hours, followed by 5‐20 days of culture at the air‐liquid interface to allow keratinocyte differentiation and stratification …”
Section: Melanoma 3d Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…We find that Stefan boundary condition [47,48]. In more realistic applications of invasion, such as malignant cellular invasion into surrounding tissues, there will be a conversion of consumed tissue into malignant cells at the interface [34,60,61,62]. One way of interpreting this conversion from tissues to cells is that there is a loss of one species, in this case the surrounding tissue, that is converted into another species, in this case invasive cells.…”
Section: Resultsmentioning
confidence: 98%
“…However, studies in vitro of metastatic melanoma showed the appearance of probable melanoma cell colonies that later cannot be found in the tissue after some days possibility invading tissue underneath (Haridas et al, 2017). In fact, our simulations are in 2D and resemble a lot the spreading of the cancer cell in a monolayer tissue, the introduction of the new dimension to make the model 3D would enhance our simulation by allowing us to study the vertical invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 95%